Microextraction Techniques for Drugs of Abuse in the ForensicPerspective: A Review - Pooja Kataria; Deepika Yadav; Tripti Bhatnagar (Indian Journal of Forensic Medicine and Pathology, 2025)
Drug-abuse is a worldwide issue that has led to many health issues and in severe cases death by overdose, suicides and homicides. These drugs can be abused by spiking them in various biological and non-biological samples. After being administered, drugs are deposited in the body through a variety of blood circulation routes. These drugs can be extracted from various biological and nonbiological samples. In the forensic perspective, it is necessary to develop a technique which can help in extraction of the drugs of abuse from these samples. This study aims at studying the various categories of drugs abused. The different extraction methods used to extract drugs from various samples are described and discussed in this article. These extraction methods cover the more resilient, contemporary, and environmentally friendly methods as well as the traditional solvent-based methods like SPME, LPME and MEP to𿿿nd out which one is the most suitable echnique. This review provides a detailed discussion of analysis techniques like LCMS and GCMS by reviewing different articles. The article analyzes the optimal circumstances, extraction conditions, bene𿿿ts, and drawbacks of several extraction ethods. Recent uses of these extraction methods are covered in the review. The systematic review approach was employed for this study which involved a qualitative approach to review the articles.